Deficiency of the promyelocytic leukemia protein fosters hepatitis c-associated hepatocarcinogenesis in mice - Herzer, Kerstin; Hofmann, Thomas G. (PLOS ONE, 2012)
Overwhelming lines of epidemiological evidence have indicated that persistent infection with hepatitis C virus (HCV) is a major risk for the development of hepatocellular carcinoma (HCC). We have recently shown that HCV core protein mediates functional inactivation of the promyelocytic leukemia (PML) tumor suppressor pathway. However, the role of PML in HCC development yet remains unclear. To clarify the function of PML in liver carcinogenesis and HCV-associated pathogenesis we crossed PML-deficient mice with HCV transgene (HCV-Tg) expressing mice and treated the resulting animals with DEN/Phenobarbital, an established protocol for liver carcinogenesis. Seven months after treatment, livers were examined macroscopically and histologically. Genetic depletion of the tumor suppressor PML coincided with an increase in hepatocyte proliferation, resulting in development of multiple dysplastic nodules in 100% of the PML-deficient livers and of HCCs in 53%, establishing a tumor suppressive function of PML in the liver. In animals expressing the HCV-transgene in PML-deficient background, HCC development occurred even in 73%, while only 7% of their wildtype littermates developed HCC. The neoplastic nature of the tumors was confirmed by histology and expression of the HCC marker glutamine synthetase. Several pro- and antiapoptotic factors were tested for differential expression and liver carcinogenesis was associated with impaired expression of the proapoptotic molecule TRAIL in PML-deficient mice. In conclusion, this study provides first in vivo evidence that the tumor suppressor PML acts as an important barrier in liver carcinogenesis and HCV-dependent liver pathology.